2016
DOI: 10.7567/jjap.55.07lc01
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of erosion mechanism of tungsten-based electrode in multiphase AC arc by high-speed visualization of electrode phenomena

Abstract: Electrode phenomena in a multiphase AC arc were successfully visualized using a high-speed observation system with a bandpass filter system to understand the erosion mechanisms of tungsten-based electrodes due to the droplet ejection and electrode evaporation. The obtained results indicated that both droplet ejection and electrode evaporation contributed to the electrode erosion in the multiphase AC arc. The erosion by droplet ejection mainly occurred during the cathodic period, while electrode evaporation mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The details of the measurement setup can be referred to in previous works. 7,20,24) 3. Results and discussion…”
Section: Measurement Of Cathode Temperaturementioning
confidence: 99%
“…The details of the measurement setup can be referred to in previous works. 7,20,24) 3. Results and discussion…”
Section: Measurement Of Cathode Temperaturementioning
confidence: 99%
“…In contrast, both electromagnetic and ion impact forces were found to increase due to the increase in the current density during arc ignition, whereas these forces suddenly disappeared during arc extinction, which in turn triggered an imbalance in the forces acting on the molten electrode and consequently led to droplet ejections. Hashizume et al [ 6 , 7 ] investigated droplet ejection from tungsten electrodes in multiphase AC arcs, in a process where 12 tungsten electrodes were arranged radially and an AC voltage of different phases was applied to each electrode to generate numerous thermal plasmas between the electrodes. In addition, the authors focused on the fact that a part of the molten electrode was extended just before the droplets were ejected, and attempted to clarify the dominant force in droplet ejection by estimating the force acting on the ridge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is expected to be utilized in nanomaterial fabrication processes owing to its high processing rate. Fundamental studies for practical use of MPA in industry have been intensively reported in terms of the arc stability (Tanaka et al, 2011), the temporal and spatial characteristics of the arc discharge (Liu et al, 2013), arc temperature fluctuation (Okuma et al, 2018(Okuma et al, , 2019, and the electrode phenomena (Tanaka et al, 2013, 2016, Hashizume et al, 2015.…”
Section: Introductionmentioning
confidence: 99%